Koyto Trangal e Sam - Dimitrova, Ralitza (Bulgaria, 2012)
A former hippie-turned-messiah, his wife and their wunderkind artist/writer/inventor son flee society on their chaotic Noah’s Ark built inside a moldy basement in downtown Sofia. He Who Travels Alone is an intimate decade-long examination of this Bulgarian family’s dogged pursuit of spiritual growth and its self-imposed exile into its own eccentricity.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films